REGULAR EXPUNGEMENT OF LEGALLY CONVICTED PERSONS – Genesis of the institute in Serbian criminal law - Samardžić, Stefan; Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In Serbian law, the term expungement is used in, at least three meanings and represents at least three institutes that are, or at least should be, dominant criminal nature. Namely, apart from expungement in criminal material law, which refers to justly convicted persons and which we denote by the term regular expungement, our legal system and legal theory also know expungement in the field of criminal procedural law which refers to the unjustly convicted persons and persons unjustifiably deprived of liberty. Finally, the third, so called special expungement of persons convicted for political or ideological reasons entered into the life of Serbian legal system more than fifteen years ago. Apart from the distinction among the mentioned institutes that bear the same name, this research aims to continue, extend and deepen the authors’ previous research and is primarily devoted to the now significantly in-depth and detailed analysis of the historical development of the institute of regular expungement of legally convicted persons in Serbian criminal law.